Sustainability Awareness and Green Information Technologies - Issa, Tomayess 1965-; Issa, Theodora 1958-; Issa, Touma B.; Isaías, Pedro (Springer International Publishing, 2020)
What is Sustainability -- Sustainability Awareness in Developed and Developing countries -- Green IT Strategies -- Green IT Technologies
Keywords: Energie; Technologie; Nachhaltigkeit; Renewable energy resources; Management; Industrial management; Computer communication systems; Technical education